Resolving Medical Disputes: Lessons from U.S. Arbitration for Indonesia’s Legal Framework - Fakih, Muhammad; Natamiharja, Rudi; Muhammad Miraj Mirza, Isroni; Pratama, Andre Arya; Oktarlina, Rasmi Zakiah (Faculty of Law, Hasanuddin University, 2025)
Arbitration serves as a dispute resolution method that offers notable benefits, especially in cases related to medical issues. In contrast, other methods such as litigation are often seen as less effective, while mediation lacks executory power due to the absence of legal enforceability, making agreements vulnerable to cancellation. In Indonesia, arbitration has not yet been adopted for resolving medical disputes, as specific technical regulations are still needed to guide relevant institutions and establish effective mechanisms. This research highlights the importance of implementing arbitration in Indonesia’s medical dispute resolution framework, using a comparative analysis of practices in the United States. Employing normative legal research with qualitative data analysis and comparative examination of international legal practices, the findings reveal that arbitration offers a binding and final resolution, making it a highly effective approach for handling medical disputes. To facilitate its adoption in Indonesia, comprehensive technical regulations and a legal framework—similar to the United States’ Uniform Arbitration Act (UAA), which outlines arbitration requirements for individual states—are necessary.